Public Transportation Crisis in Bandar Lampung - Ida Bagus Ilham Malik (University of Bandar Lampung (UBL), 2013)
Increasing the number of private vehicles are not comparable with the growth of public transport vehicles. Though the population of the city has increased rapidly, followed by increasing the amount of movement of people from one place to another. This growing movement should be facilitated by public transport so that traffic is not crowded by private vehicle. Because with more and more use of private vehicles will have an impact on the wasteful use of fuel for motor vehicles, traffic congestion led to wastage of time and cost, as well as environmental pollution. Therefore, the development of public transport in urban areas should be done as soon as possible to address the addition of the urban population, increasing the number of movements of people to move from one place to another, and the increase in the number of private vehicles.